Effect of protein peptides with different molecular weights on the setting and hydration process of gypsum. (7th February 2022) - Ding, Xiaoliang; Wei, Bangquan; Deng, Minggao; Chen, Hui; Shan, Zhihua
Highlights: Molecular weight- retarding property relationship of protein peptide was studied. Molecular weight plays an important role in gypsum retardation. Low-molecular-weight protein peptide more effectively inhibited gypsum hydration. Abstract: A series of protein retarders were prepared by hydrolyzing gelatin (Gel: Mw  = 68020 g/mol; Gel-3: Mw  = 40777 g/mol; Gel-6: Mw  = 11951 g/mol and Gel-9: Mw  = 7785 g/mol), and then the effects of these protein retarders on the setting and hydration process of gypsum were investigated in this paper. With the decreasing molecular weight of the protein retarder, the retarding effect on gypsum increased, while the negative impact on the strength and crystal morphology was more significant. The presence of a low-molecular-weight protein retarder more effectively delayed the increase in hydration degree of gypsum. FTIR and XRD analysis indicated that the formation of hydration product (gypsum dihydrate) was inhibited due to the addition of protein retarder. Moreover, this inhibition was more remarkable when a protein retarder with a lower molecular weight was introduced. Furthermore, we discovered that low-molecular-weight protein retarder with more carboxyl groups more easily chelated calcium ions in the gypsum paste, thereby more effectively inhibiting the hydration reaction of gypsum hemihydrate. In general, the molecular weight of the protein retarder plays an important role in gypsum retardation.